Incidence of carcinoma breast in females presenting with breast lumps - Alam, Ashraful Sylvia; Sharmin, Farzana; Faruq, Tima (Journal of Chittagong Medical College Teachers’ Association, 2011)
Keywords: breast lumps; infiltrating duct carcinoma; fibrocystic disease DOI: http://dx.doi.org/10.3329/jcmcta.v22i1.9108 JCMCTA 2011; 22(1): 25-27